OPEC : The Failing Giant - Ahrari, Mohammed E. (Book collections on Project MUSE., 2015)
A glut of oil, dropping prices, the threat of insolvency, a divided membership -- these developments in the early weeks of 1985 underline the cogency of Mohammed Ahrari's historical study of the OPEC oil cartel and his argument that economic forces, not politics, determine OPEC's action in the world arena. The impetus for the formation of OPEC in 1960 was the desire of the oil-producing states for greater income from their most valuable resource. The international oil corporations had secured lucrative concessions early in this century, and in the 1960s they still dictated both the terms of pro.